Auditory affective processing, musicality, and the development of misophonic reactions - Mednicoff, Solena D.; Barashy, Sivan; Gonzales, Destiny; Benning, Stephen D.; Snyder, Joel S.; Hannon, Erin E. (Frontiers in Neuroscience, 2022)
Misophonia can be described both as a condition and as a negative affective experience such as feeling irritation or disgust in response to hearing certain sounds, such as eating, drinking, gulping, and breathing. Although the earliest misophonic experiences are often described as occurring during childhood, relatively little is known about the developmental pathways that lead to individual variation in these experiences. This literature review discusses evidence of misophonic reactions during childhood and explores the possibility that early heightened sensitivities to both positive and negative sounds, such as to music, might indicate a vulnerability for misophonia and misophonic reactions. We will review when misophonia may develop, how it is distinguished from other auditory conditions (e.g., hyperacusis, phonophobia, or tinnitus) and developmental disorders (e.g., autism spectrum disorder or Williams syndrome), and we explore the possibility that children with heightened musicality could be more likely to experience misophonic reactions and develop misophonia.